If x^3-2x^2-5x+6 has x = 1 as one root find the other roots.

### 1 Answer | Add Yours

`x^3-2x^2-5x+6 = 0`

`x^3-x^2-x^2-5x+6 = 0`

`x^2(x-1)-(x^2+5x-6) = 0`

`x^2(x-1)-(x^2+6x-x-6) = 0`

`x^2(x-1)-(x-1)(x+6) = 0`

`(x-1)(x^2-x-6) = 0`

`(x-1)(x^2-3x+2x+6) = 0`

`(x-1)(x(x-3)+2(x-3)) = 0`

`(x-1)(x-3)(x+2) = 0`

So the roots are x = 1, x = 3 and x = -2.

*The other two roots is x = 3 and x = -2.*

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes